COMPARATION INKUIRI-BELDING LEARNING MODELS WITH JIGSAW COOPERATIVE MODELS ON PHYSICS LEARNING RESULTS OF X SMAN 1 2x11 ENAM LINGKUNG - Jumarlis, Jumarlis (PILLAR OF PHYSICS EDUCATION, 2024)
The capacity of educators to strategize and execute instructional sessions is essential in determining the academic achievements of students. Teachers can improve learning outcomes by choosing a suitable instructional model that is in line with the learning goals and the content to be delivered in the classroom. The objective of this study is to examine the disparities in physics learning achievements among Grade X students at SMAN 1 2x11 Enam Lingkung who were instructed using the Guided Inquiry model versus those who were instructed using the Jigsaw Cooperative learning model. This study used a quasi-experimental methodology employing a posttest-only control design. The study sample comprises Grade X students enrolled at SMAN 1 2x11 Enam Lingkung for the academic year 2023/2024. The sample was chosen via purposive sampling, with Class X.1 as the first experimental group and Class X.2 as the second experimental group. The research data comprises the academic achievements of students in the field of knowledge. Examples of data gathering equipment encompass the utilization of multiple-choice examinations. The employed data analysis procedures include descriptive analysis, normality test, homogeneity test, and hypothesis testing with a significance level (α) of 0.05. The data analysis indicates that the average learning outcomes for the first experimental group were 75.429, but for the second experimental group, it was 65.000. The results of the hypothesis testing conducted on the posttest scores indicated that the calculated t-value (t_calculated) was 3.781, which was more than the critical t-value (t-table) of 2.010. This suggests that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. There is a notable distinction between pupils instructed using the Guided Inquiry style and those taught with the Jigsaw Cooperative learning methodology for the subject of alternative energy.